Identification of EU bank business models: A novel approach to classifying banks in the EU regulatory framework - Marina Cernov; Teresa Urbano (European Banking Authority (EBA), 2018)
This paper proposes a standardised classification of business models of the European Union (EU) banks. Our work is based on a rich and unique dataset collected for the first time for the full population of EU banks at individual level. The proposed approach to classification combines both a qualitative and a quantitative component, which is a new approach compared with relevant literature in business model identification and classification. The qualitative component is based on an expert knowledge of the supervisory authority, which is confirmed or challenged by quantitative indicators. Our findings are that banks' classification through this mixed approach allows better and more granular identification of banks' business models than the clustering methodology, which is more commonly used in the literature. The business model categorisation can provide the supervisory and regulatory authorities with a benchmark for classifying institutions for a more structured and consistent approach to regulatory impact assessment, analysing trends and risks, proportionality, and supervision, ensuring the continuity and comparability of results over time.
Keywords: 330; Business models; business model analysis; EU banks; clustering; regulation; impact assessment; proportionality; peer review